Desain Sarana Antar Jemput Pakaian Laundry Kiloan (Studi Kasus Laundry Rumah Cuci Surabaya) - Hamdan Bahalwan; Achmad Akmal Almahdi (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2023)
Laundry kiloan is a laundry service that calculates clothes based on kilograms. This kilo laundry service has an affordable price compared to individual laundry services. The laundry service process is faster because all the clothes are washed at the same time. Problems encountered in the field when picking up laundry items include laundry items often falling, plastic bags often being torn by motorbike nuts, being splashed with water, and there being no tools to weigh laundry items during laundry pick-up and drop-off, and there being no facilities. pick up and drop off laundry clothes as a place to put laundry clothes, only relying on the front seat of the motorbike. The solution to this problem was a design for a laundry pick-up and drop-off facility. This design was designed using qualitative and quantitative research methods. Qualitative research is research that produces problematic or written information about people and behavior observed in the field, while quantitative data is data that can be analyzed statistically or from the results of questionnaires which become supporting data in research. This data will then be analyzed and become the focus of the research. Observations were carried out in two places, namely Rumah Cuci Surabaya as a case study and Kendil Washing Clinic Gresik as a place for needs analysis, material analysis, shape analysis, color analysis, dimensional analysis, technology analysis, ergonomic, and anthropometric analysis, placement analysis, security analysis, identity analysis, and system analysis. The results of the research are the design of a side box and top box type of laundry pick-up and delivery facility, made from jeep hood fabric and Eva sponge, using a zipper system, Velcro, buckle, webbing rope as reinforcing rope, and wooden sticks as support.